Anti-corrosion ceramic coatings on the surface of Nd-Fe-B repelling magnets - Taran, A.V.; Garkusha, I.E.; Taran, V.S.; Timoshenko, O.I.; Misiruk, I.O.; Skoblo, T.S.; Romaniuk, S.P.; Starikov, V.V.; Baturin, A.A.; Nikolaychuk, G.P.; Pyvovar, N.V.; Gnidenko, Yu.P. (Вопросы атомной науки и техники, 2019)
The results of vacuum-arc deposition of thin ZrO₂ coatings to protect the surface of Nd-Fe-B permanent magnets used as repelling devices in orthodontics are presented. The structure, phase composition and mechanical properties of zirconium dioxide films have been investigated by means of SEM, XRD, EDX, XRF, and nanoindentation method. It was revealed the formation of polycrystalline ZrO₂ films of monoclinic modification with average grain size 25 nm. The influence of the ZrO₂ coating in terms of its barrier properties for corrosion in quasi-physiological 0.9 NaCl solution has been studied. Electrochemical measurements indicated good barrier properties of the coating on specimens in the physiological solution environment.